Задача выбора иерархической структуры многопродуктовой коммуникационной сети с мелкопартионными дискретными потоками - Васянин, В.А.; Трофимчук, А.Н. (Екологічна безпека та природокористування, 2012)
In work is considered and experimentally investigated the problem of a choice of hierarchical structure of a multicommodity network with small packages of flows. The mathematical model of a problem is offered and the general circuit of heuristic algorithm of its decision is developed. On the basis of the proved statement, that the choice of structure of a network poorly depends on bandwidths of its arches, the initial problem is replaced with more simple, for decision of which the algorithms of optimization of packings may be used. The received results may be applied at designing structure of real transport networks and data networks.